2012
DOI: 10.1016/j.sleep.2012.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Familial risk of sleep-disordered breathing

Abstract: Contributor´s Statement PageKarin Lundkvist, MD: Has contributed to conception and design, analysis and interpretation of data and drafting the article and final approval of the version to be published.Kristina Sundquist, MD, PhD: Has contributed to conception and design, acquisition of data, analysis and interpretation of data, revising the article critically for important intellectual content and final approval of the version to be published.Xinjun Li, MD, PhD: Has contributed to conception and design, analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
2
14
0
2
Order By: Relevance
“…In agreement, we found that the prevalence of rhinitis was higher in children born by Caesarean section, those with fewer siblings and those whose parents had more education and higher income. On the other hand, children whose parents had more education and higher income had a decreased risk of OSAS, consistent with previous studies which examined the relationship of OSAS and socio‐economic status …”
Section: Discussionsupporting
confidence: 91%
“…In agreement, we found that the prevalence of rhinitis was higher in children born by Caesarean section, those with fewer siblings and those whose parents had more education and higher income. On the other hand, children whose parents had more education and higher income had a decreased risk of OSAS, consistent with previous studies which examined the relationship of OSAS and socio‐economic status …”
Section: Discussionsupporting
confidence: 91%
“…This might be due to an underpowering of that group. Previous pediatric studies have reported a higher prevalence of both SDB and OSA in males, although it has been hypothesized that this difference happens mostly at puberty with hormonal changes [26,37]. However, a few studies have concentrated on infants and have also shown a male preponderance for snoring and OSA [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Also, low socioeconomic status and race seem to influence the incidence of prenatal and perinatal complications [20]. A recent study also indicates familial clustering of SDB (SDB caused by adenotonsillar or tonsillar hypertrophy), which is an important information for clinicians [21]. …”
Section: Discussionmentioning
confidence: 99%